Public benefits of private technology adoption: Spatial externalities of water conservation in India - Bhargava, Anil K.; Lybbert, Travis J.; Spielman, David J. (World Scientific Publishing, 2023)
With growing pressure on groundwater resources in developing countries, water-conserving technologies (WCTs) seem to be an especially promising method of both poverty alleviation and agricultural adaptation to risks associated with climate change. While the private benefits of technology adoption are increasingly understood by both farmers and policymakers, the public benefits — or positive spillovers that additionally affect non-adopters and adopters alike — are often overlooked, thus understating the case for investment in their development and promotion. This paper explores the physical and socioeconomic conditions that shape the distribution of these benefits locally and across landscapes, pointing to the importance of integrating spatial relationships and underlying economic conditions into their estimation. We focus on India — the world’s largest user of groundwater — and build a spatially-sensitive hydroeconomic model to capture the dynamics of public water availability and extraction costs due to WCT adoption. We calibrate our model using household-plot level survey data and randomized control trial impact estimates from a rollout of WCTs in the Indo-Gangetic Plains. Geo-referenced borewell locations and a novel farmer pumping survey allow us to scale results to the landscape level. Results show that public benefits from WCT adoption initially occur primarily via reduced well interference and that clustering of WCTs in dense, low-income farming areas can generate the highest mix of private and public benefits. With most farmers in this study boring wells and pumping water without local spatial consideration, policymakers with the dual objectives of climate change adaptation and poverty alleviation may consider these dual environmental and economic water-conserving agricultural technology benefit spillovers.